Alonso de Zorita, his major works and the Indian politics of Philip II (1561-1585) - Atilano Gutiérrez, José Enrique; Terán Elizondo, María Isabel (Revista de historia., 2025)
This article takes into consideration the lines of research proposed by the Indian and Novo-Hispanic historiography of the second half of the 16th century, in which the circulation of royal information through manuscripts presented by officials of the Audiences of the New World to the peninsular courts is highlighted. The case study proposed for this research is the documentary corpus of the Cordovan Alonso de Zorita (¿1512-1585?), who served as oidor of the Audiencias of Santo Domingo, Guatemala and Mexico for almost twenty years (1556-1566). Each of the works to be analyzed here reflects a particular political situation of the Indian Orb, since the topics dealt with in them are closely related to the problems dealt with by the Hispanic Crown during the second half of the 16th century. Those years coincide with a period of reforms, all of them made with the intention of improving the Indian economic and political administration; and, also, with the intentions of an oidor to join the possible benefits resulting from those changes. Finally, our purpose is to study, relying on textual criticism, historiography and ecdotics, the diverse historical and political contexts in which Zorita’s work was created and, thus, to create a proposal of reading sense that allows every reader interested in these topics to find an accompaniment in the analysis of this type of documentary sources.